2021
DOI: 10.1051/e3sconf/202125401008
|View full text |Cite
|
Sign up to set email alerts
|

Research and restocking of wheat varieties to pathogens of especially dangerous fungal diseases

Abstract: Based on the results of immunological assessments and rejection of the material by phenotype, 327 sources and 79 donors of immunity were selected from spring wheat, 27 and 23 from winter wheat, respectively. Applying PCR diagnostic method, Lr genes were found in the selected samples of spring wheat. Screening revealed the presence of the following genes in the studied samples. They are Lr9, Lr19, Lr24, Lr 34, Lr1, Lr10, Lr20 and Lr26. Within selection samples of the Central Russian branch, the prevalence of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is worth noting that RR did not appear as abnormal mitochondria until 8-15 dpi (Figure 4), suggesting that RR has a stronger capacity in resisting rust pathogen infection than RS. Studies on fungal diseases demonstrated that increasing respiration was a basic response to injury in most infected host tissues [27]. The increase and aggregation of mitochondria were observed in RR and RS at a later stage of infection, which might be due to the enhanced respiration at the infected site caused by pathogen infection.…”
Section: Leaf Cell Structure and Physiological Changes After Inoculat...mentioning
confidence: 94%
See 1 more Smart Citation
“…It is worth noting that RR did not appear as abnormal mitochondria until 8-15 dpi (Figure 4), suggesting that RR has a stronger capacity in resisting rust pathogen infection than RS. Studies on fungal diseases demonstrated that increasing respiration was a basic response to injury in most infected host tissues [27]. The increase and aggregation of mitochondria were observed in RR and RS at a later stage of infection, which might be due to the enhanced respiration at the infected site caused by pathogen infection.…”
Section: Leaf Cell Structure and Physiological Changes After Inoculat...mentioning
confidence: 94%
“…Previous studies have shown that even minor damage to photosynthesis can weaken the defense systems and increase the susceptibility of the plants to pests and pathogens [27]. The chloroplast disorder led to the change or rearrangement of the chloroplast ultrastructure, which could be related to the development of plant symptoms after pathogen infection [29].…”
Section: Leaf Cell Structure and Physiological Changes After Inoculat...mentioning
confidence: 99%